Pad foundation process for klinik kesihatan 3 Rantau Panjang Kelantan / Mohd Faiz Mohd Juhari - Mohd Faiz, Mohd Juhari (2018)
The purpose for this Practical Training (BSR 360) is to make sure what I have learn from 1st Semester till 5th Semester can be applied during my internship. The other reasons is to gain a new knowledge and experience in my workplace and how to communicate with people and coworker. It is compulsory for building survey to carry this report because it gave 40% from total mark before we graduate. As conclusion by doing this Practical Training, I gain more information and knowledge about the how to manage project, sell quotation document and much more. I fell so glad because from this internship, I have knew everything on how to solve problem, how to work with professional workers and others. I hope that this report which has been done are followed requirement that are need by task and lecturer are satisfied with my report.